High areal specific capacity of Ni3V2O8/carbon cloth hierarchical structures as flexible anodes for sodium-ion batteries. Issue 30 (21st July 2017) - Zhou, Chengshuang; Fan, Shaoxun; Hu, Mingxiang; Lu, Jiamin; Li, Jia; Huang, Zheng-Hong; Kang, Feiyu; Lv, Ruitao
Abstract : We report a two-step synthesis of Ni3 V2 O8 @CC as a flexible electrode for sodium ion batteries with high loading density and areal specific capacity. Abstract : Due to the low density of nanostructured materials, it is still a big challenge to realize high volumetric performance instead of high specific gravimetric capacity with many state-of-the-art electrodes for compact electrochemical energy storage. Moreover, developing high-performance flexible and binder-free electrode materials is also crucial for their future applications in diverse fields, such as portable electronics and wearable devices. In this work, we designed and synthesized a Ni3 V2 O8 /carbon cloth (CC) hierarchical structure as a flexible anode for sodium-ion batteries. Morphology-controllable growth of different Ni3 V2 O8 /CC hierarchical structures is achieved by optimizing the synthesis parameters ( e.g. the growth temperatures). The high mass loading (4 mg cm −2 ), ultra-high areal specific capacity (2.6 mA h cm −2 at a current density of 500 mA g −1 ), no addition of binders or other additives and good flexibility facilitate their application in sodium-ion batteries.